2011
DOI: 10.1002/ar.21411
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Olfactory and Nonolfactory Surface Area in the Nasal Fossa of Microcebus murinus: Implications for Microcomputed Tomography and Airflow Studies

Abstract: The nasal fossa of most mammals exemplifies extreme skeletal complexity. Thin scrolls of bone (turbinals) that both elaborate surface area (SA) and subdivide nasal space are used as morphological proxies for olfactory and respiratory physiology. The present study offers additional details on the nasal fossa of the adult mouse lemur (Microcebus murinus), previously described by Smith and Rossie (Smith and Rossie [2008]; Anatomical Record 291:895-915). Additional, intervening histological sections of the specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 27 publications
(61 reference statements)
1
50
0
Order By: Relevance
“…Our study shows that variations in the size of the olfactory recess likely have significant functional consequences in groups that exhibit extensive variation in olfactory recess size, such as bats and primates (Cave, 1973;Moore, 1981;Smith et al, 2011;Smith et al, 2012;Smith et al, in press). This work also adds to the growing body of computational modeling studies that investigate the role of morphology in airway function.…”
Section: Research Articlementioning
confidence: 74%
“…Our study shows that variations in the size of the olfactory recess likely have significant functional consequences in groups that exhibit extensive variation in olfactory recess size, such as bats and primates (Cave, 1973;Moore, 1981;Smith et al, 2011;Smith et al, 2012;Smith et al, in press). This work also adds to the growing body of computational modeling studies that investigate the role of morphology in airway function.…”
Section: Research Articlementioning
confidence: 74%
“…Thus, the short snout of feliforms appears to have reduced the space available for the maxilloturbinal, allowing the anterior ethmoturbinals to lie in the respiratory air pathway (Fig. ), a pattern also observed in some primates (Smith et al, ).…”
Section: Comparative Anatomy and Functionmentioning
confidence: 74%
“…These turbinals are the primary location for olfactory epithelium, but may also participate in respiratory air‐conditioning in some primates (Smith et al, ; DeLeon and Smith, ) and short‐snouted carnivorans (Van Valkenburgh et al, ). In addition, olfactory epithelium can be found rostrally on the nasal septum as well as lining various recesses and the lateral walls of the nasal cavity (Adams, ; Bhatnagar and Kallen, ; Smith et al, ). In many or most mammals, the nasoturbinal has a tube‐like morphology and appears to function in directing air to the posteriorly positioned olfactory region.…”
Section: Comparative Anatomy and Functionmentioning
confidence: 99%
“…The architecture of the turbinals and floor of the nasal capsule determines whether orthonasal and/or retronasal air currents pass directly over olfactory epithelium. Turbinals are highly variable between mammalian clades, and only recently has 3D imaging made morphological analysis possible (Van Valkenburgh et al, 2004; Rowe et al, 2005; Smith et al, 2011; Eiting et al, 2015), and shown that they preserve phylogenetic (Macrini, 2012) and ecological (Van Valkenburgh et al, 2011) signals.…”
Section: Resultsmentioning
confidence: 99%
“…They lie directly in the stream of ortho-retronasal airflow and function in metabolic heat and water balance (Smith et al, 2011; Eiting et al, 2015). Saturation of air within the nose may also play a role in volatilization, but experimental airflow studies are still in their infancy.…”
Section: Resultsmentioning
confidence: 99%